Isozyme variation between two closely related species Crang on Crangon (L.) and Crangonallmanni Kinahan (Decapoda, Caridea) - Abdullah, Rosmann; Shukor, Nor Aini A.B. (Brill Academic Publishers, 1993)
Crangon crangon(L.) and C. allmanni Kinahan were screened at 11 enzyme loci for electrophoretically detectable variation. The mean observed heterozygosity was 0.1346 + 0.06295 in C. crangonand 0.0567 + 0.0352 in C. allmanni.The possible causes of these rather low levels of genetic variation are considered in relation to the physical factors and feeding behaviour. The results also suggest that C. crangonand C. allmanni are two separate species that differ genetically although morphologically similar.